2012
DOI: 10.1155/2012/835290
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Urinary Sphincter: Long-Term Results and Patient Satisfaction

Abstract: The published evidence concerning the safety, efficacy, and patient satisfaction for implantation of the current model of the artificial urinary sphincter (AS 800) in men with post prostatectomy urinary incontinence was the objective of this review. A Pub Med English language literature search from 1995 to 2011 was performed. A majority of men who undergo AUS implantation for post prostatectomy urinary incontinence achieve satisfactory results (0 to 1 pad per day). Infection rates range from 0.46 to 7%, cuff e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Injection therapy with bulking agents is suggested to be performed in patients with minimal incontinence or for short‐term improvement for patients in poor health status, die to the therapy's low cure rates and deterioration over time . AUS has been shown to have the highest success rates among all available surgical treatment options for SUI, however, it has complications (including erosion, mechanical failure and infection) with rates as high as 37% within the first 48 months from implantation . Over time, the adoption of sling procedures has increased considerably .…”
Section: Introductionmentioning
confidence: 99%
“…Injection therapy with bulking agents is suggested to be performed in patients with minimal incontinence or for short‐term improvement for patients in poor health status, die to the therapy's low cure rates and deterioration over time . AUS has been shown to have the highest success rates among all available surgical treatment options for SUI, however, it has complications (including erosion, mechanical failure and infection) with rates as high as 37% within the first 48 months from implantation . Over time, the adoption of sling procedures has increased considerably .…”
Section: Introductionmentioning
confidence: 99%
“…These component changes include narrow back cuffs for bulbous urethral use, smaller (3.5 and 4.0 cm) cuffs, surface-coated cuffs to reduce wear, kink-resistant tubing, tubing sleeves to reduce wear, and sutureless connectors to facilitate making connections and to reduce connector failures. Montague [7] reported that Kaplan-Meier 5-year projections for freedom from any reoperation were 50% for a small series. Complications of artificial urinary sphincter include cuff erosion, infection, urethral atrophy, and mechanical failure.…”
Section: Discussionmentioning
confidence: 99%
“…Late erosions (several months to years) are caused by urethral atrophy such as that encountered after radiation therapy, small AUS cuff, and urethral catheter placement without prior deactivation of the AUS. 37 A special consideration for AUS placement is the combination with bladder augmentation with small bowel. Catto and colleagues 42 reported on 86 patients who underwent bladder augmentation and AUS placement, of whom in 56 (65%) patients the AUS was placed simultaneously.…”
Section: Infections and Erosions Due To Artificial Urinary Sphinctersmentioning
confidence: 99%